Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0009922815598143
|View full text |Cite
|
Sign up to set email alerts
|

The Therapy Beneath the Fun

Abstract: The study advances the need to incorporate medical clowns as an integral part of medical teams performing invasive procedures and to include clowns in all stages of the hospital visit when children undergo invasive examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 37 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…In other countries, for instance Israel, medical clowns are involved in medical procedures, and they cooperate closely with hospital staff. Studies have shown positive effects of these activities on the children, and it has been suggested that medical clowns should become an integral part of the health team (Kocherov et al, 2016; Ofir et al, 2016; Tener, Ofir, Lev-Wiesel, Franco, & On, 2016; Wolyniez et al, 2013). However, other studies showed a more negative attitude and suggested that the presence of clowns may interfere with medical routines and that children did not want a clown present during tests or medical procedures (Mansson et al, 2013; Vagnoli et al, 2005; Van Venrooij & Barnhoorn, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other countries, for instance Israel, medical clowns are involved in medical procedures, and they cooperate closely with hospital staff. Studies have shown positive effects of these activities on the children, and it has been suggested that medical clowns should become an integral part of the health team (Kocherov et al, 2016; Ofir et al, 2016; Tener, Ofir, Lev-Wiesel, Franco, & On, 2016; Wolyniez et al, 2013). However, other studies showed a more negative attitude and suggested that the presence of clowns may interfere with medical routines and that children did not want a clown present during tests or medical procedures (Mansson et al, 2013; Vagnoli et al, 2005; Van Venrooij & Barnhoorn, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Children, family and healthcare professionals described the clown visits as moments of fun and distraction (Ford, Courtney-Pratt, Tesch, & Johnson, 2014; Ofir, Tener, Lev-Wiesel, On, & Lang-Franco, 2016). The clowns tailored their play to the situation, created a bond with the child and reframed the meaning of the medical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…One third of the studies targeted specifically the benefits of the intervention of hospital clown for children [17,[19][20][21][22]27,29,30]. Over half of the studies reported intervention benefits of hospital clown for children and their parents [5,[11][12][14][15]18,[23][24][25][26]28,[31][32][33][34]. Four other studies have evaluated in addition the opinions of health professionals [4,10,13,16].…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…Thirty six percent of studies were focused on invasive medical procedures including venous blood sampling, intravenous catheter, burn, wound dressing, immobilization of injured limbs, wound suture and blood tests [15][16]23], medical forensic examiner (allegedly abused children) [5,[24][25], allergy prick skin tests 28, botulinum toxin injections 30, intra-articular corticosteroid injection 20, magnetic resonance imaging 17. Thirty two percent of studies targeted non-invasive procedures [4,19,26,27,29,[31][32][33][34].…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation